(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Contemporary Kazakhstan endures process of transformation of all spheres of life of society, including mass and individual consciousness which is expressed in emergence of new tendencies in philosophy, sciences, education, art, religion, politicians and economies. All this demands the serious scientific analysis and studying. Authors consider in article and actively discussed new trends as «innovations», the «innovative development» and «innovative society» which increased recently in mass consciousness of the Kazakhstan society. Any new concept or any new concept always demands judgment and an explanation, and this mission of philosophy. The new view and outlook, a new formation of thinking «innovative» is necessary for understanding of innovations. Many people mean «innovative» only in understanding of technical innovations which use is obvious not enough to full innovative development of society. In understanding of authors «the innovative thinking» creates not just new, and essentially new on the basis of which does not have the previous analogs. Key words: innovative thinking, innovations, innovative development, education transformation, modern Kazakhstan society.